Effect of post-annealing treatment on the structure and luminescence properties of AIN: Tb 3+ thin films prepared by radio frequency magnetron sputtering - Tucto Salinas K.Y. (2017)
This work was funded by the Peruvian science foundation FONDECYT under the projects “Círculos de investigación en ciencia y tecnología-2”, contract number 011-2014 and under the cooperation project with the German academic exchange service (DAAD), contract number 035-2016. The authors also gratefully acknowledge the support of Karem Tucto and Loreleyn Flores by CONCYTEC under the contract numbers 012-2013-FONDECYT and 000236-2015-FONDECYTDE, respectivley.